Immunocytochemical Localization of Claudin-1 in the Maturation Ameloblasts of Rat Incisors - Nishikawa, Sumio; Abe, Michio (Frontiers in Physiology, 2010)
Claudin 1 is a tight junction transmembrane protein. Its localization in the maturation ameloblasts of rat incisors was examined by immunofluorescence microscopy. Distal junction area of ruffle-ended ameloblasts (RA) and the Golgi apparatus of a sub-population of smooth-ended ameloblasts (SA) and RAs stained positive with anti-claudin 1 antibodies. Since it has been shown that ameloblasts repeatedly alternate between an SA and an RA morphology during enamel maturation, the presence of claudin 1 in the Golgi cisterns may indicate the presence of tight junction precursors before transportation to the junctional area.